Evaluation des connaissances des médecins généralistes concernant l’utilisation des sympathomimétiques au cours des état de choc au niveau de service des urgences médico-chirurgicale hôpital 240lits mixte Akid Lotfi - BOUSMAHA Bouchra (My University, 2023)
Shock is a serious pathology with a high mortality rate. Optimization of their management in the hospital phase. A study of the medical literature has enabled us to detail the current state of knowledge concerning the physiopathology of states of shock, the therapeutics available and, finally, to identify the strategies that can be used in emergency medicine. We conducted a practice survey in 2023 among practicing to compare our practices. Our survey revealed significant differences in the therapeutics used by GPs. legitimate in this context. Several procedures are necessary.They meet a triple objective of updating and harmonizing the practices of our UMC department, and optimizing the early management of these heavy patients. The difficulty of choosing a sympathomimetic is a case frequently encountered in medical practice, where the physician is always the sole judge of the benefit-risk balance of a therapy in a given clinical situation, provided he has a good knowledge of the products available to him